Geochemical evidence for the origin of the IIE parent body from H chondrite‐like material. (31st July 2022) - Teplyakova, S. N.; Humayun, M.; Lorenz, C. A.; Ivanova, M. A.
Abstract: Isotopic compositions of O, Mo, and Cu in the IIE iron meteorites have indicated a close affinity to the H chondrite group. The diversity of trace element compositions and their abundance of silicate inclusions indicate that IIE iron meteorites were formed in multistage processes. To better constrain the formation of the IIE irons, this study analyzed elemental abundances in the metal of five IIE irons (Elga, Miles, Tobychan, Verkhne Dnieprovsk, and Watson) by laser ablation inductively coupled plasma mass spectrometry. The data are interpreted in terms of a new model of IIE crystallization from the metal fraction of completely molten H chondrite‐like material based on the solid/liquid distribution coefficients of siderophile and chalcophile elements changing simultaneously with changes of S concentrations in the remaining liquid during the crystallization of the Fe, Ni phase in the Fe‐Ni‐S system. The model showed that IIE iron compositions could be produced as solid phases at 40–73 wt% of fractional crystallization of the metal component of a bulk H chondrite‐like metallic melt. We propose that IIE iron metal could have originated from the solidified core of a differentiated body of H chondrite‐like composition and sampled different fractions of that core exposed during a catastrophic disruption of the body. The present structure of metal and silicate inclusions of IIE irons was formed by remelting and metal–silicate mixing during late impact event(s) on the parent body surface.